Massive Flash Neurogenic Pulmonary Edema after Subarachnoid Hemorrhage - Subedi, Shradha; Kumar Thapa, Dinesh; Tamrakar Karki, Karuna (Eastern Green Neurosurgery, 2024)
Neurogenic pulmonary edema is a rare condition associated with subarachnoid hemorrhage secondary to intracranial aneurysm rupture posing high mortality rate. Management of flash pulmonary edema immediately after ictus of spontaneous subarachnoid hemorrhage is very challenging. Here, we reported a rare case of a 47- year-old lady who had massive immediate pulmonary edema following spontaneous subarachnoid hemorrhage.